Utilization of foliar cuticle morphology for the identification of weedy grasses. Issue 7 (1st April 2019) - Khan, Raees; Kiliç, Ömer; Abidin, Sheikh Zain Ul; Ullah, Asad; Ullah, Hadayat; Zafar, Muhammad; Ahmad, Mushtaq; Khan, Shujaul Mulk
Abstract: For the robust identification of weeds of taxonomically complex families like Poaceae, scanning electron microscopy (SEM) and light microscopy (LM) are of significant implications. In this study, SEM and LM methods were used by investigating 12 Pakistani weedy grass species as an example for foliar epidermal micromorphological characters for its role in the identification of grasses species. Qualitative and quantitative foliar micromorphological variations in stomatal type, number, guard cells, subsidiary cells, silica bodies and trichomes were studied. Significant variation was observed in both qualitative and quantitative features and based on this diversity in epidermal characters, a key was drawn to delimitate the species. Variations in stomata, silica bodies (SiO2 · n H2 O), macrohairs, microhairs, hooks, papillae, prickles, and other epidermal structures were used in establishing the taxonomic key. The data were also statistically evaluated by determining its mean, standard deviation, variance, the coefficient of variance, and standard error. Foliar epidermal characters such as silica bodies shape and trichomes were taxonomically more useful than stomatal types, subsidiary, and guard cells. SEM and LM micromorphological characters were of substantial importance in the delimitation of closely related species. Abstract : Grassy weeds are very difficult to identify as they are mostly in the vegetative stage. Light and scanning electron microscopic investigations of the leaf cuticles of 12 weedy grasses have been done. The investigated characters were found useful in the identification of these weedy grasses.